Emancipation from work or emancipation through work? Aesthetics of work and idleness in recent French thought - Lane, Jeremy F. (Edinburgh University Press, 2016)
In Le Capitalisme cognitif (2007), Yann Moulier Boutang argues that, under Post-Fordism, workers are expected to invest ever more of their creative, affective, and cognitive powers in their labours. These eminently human qualities, he maintains, are inherently resistant to capture and exploitation by capitalism. Hence, their integration into the capitalist system risks provoking that system’s downfall, heralding the emergence of an Aesthetic State in which work itself will be modelled on disinterested creative activity and genuine emancipation will follow. Moulier Boutang is a leading representative of the French brand of néo-opéraïste thought and his work typifies the manner in which néo-operaïstes understand the relationships between work, aesthetics, and political emancipation. This is an understanding that stands in stark contrast to the work of Jacques Rancière. For Rancière, emancipation can only come through an escape from work, in moments of idleness that are prefigured in the disinterested nature of aesthetic experience. This article will examine the nature and stakes of this striking contrast between Moulier Boutang’s ‘aesthetics of work’ and Rancière’s ‘aesthetics of idleness’, between the former’s belief in the possibility of emancipation through work and the latter’s focus on the possibilities of emancipation from work.